Pengaruh Pola Asuh Orang Tua dan Persepsi Siswa tentang Kepribadian Guru terhadap Karakter Siswa di Madrasah Aliyah Hasanah Pekanbaru - Chodijah Nasution (AL-USWAH: Jurnal Riset dan Kajian Pendidikan Agama Islam, 2022)
This research aims to know if there is or there is no positive and significant effect of parents’ parenting pattern and students’ perception about teacher’s personality towards students’ characteristics at Madrasah Aliyah Hasanah Pekanbaru. There are three formulation of research problems namely; 1) if there is effect of parent’s parenting pattern towards students’ character at Madrasah Aliyah Hasanah Pekanbaru, 2) if there is effect of students’ perception about teacher’s personality towards students’ character at Madrasah Aliyah Hasanah Pekanbaru, 3) if there is effect between parent’s parenting pattern and students’ perception about teacher’s personality towards students’ character at Madrasah Aliyah Hasanah Pekanbaru. This research was a correlational research with quantitative approach. The research population were 71 students. The research samples were 61 students. Sample selection was by using Slovin formula with error level 5%. The technique of sample selection was Proportionate Stratified Random Sampling. The technique of data collection was by using questionnaire, observation, and documentation. The technique of data analysis used multiple regression. The research results obtain: 1) there is positive and significant effect of parent’s parenting pattern towards students’ character by obtaining r count 0,383 > r table 0,254, then Ha is accepted and Ho is rejected, 2) there is no significant effect of students’ perception about teacher’s personality towards students’ character by obtaining r count 0.107 < r table 0,254, then Ha is rejected and Ho is accepted, 3) there is positive effect between parent’s parenting pattern and students’ perception about the teacher’s personality altogether towards students’ character with Fcount 5,328 > Ftable 3,15, then Ha is accepted and Ho is rejected. The amount of determination coefficient number (R square) is 0, 155 or the same with 15,5%.TRANSLATE with x EnglishArabicHebrewPolishBulgarianHindiPortugueseCatalanHmong DawRomanianChinese SimplifiedHungarianRussianChinese TraditionalIndonesianSlovakCzechItalianSlovenianDanishJapaneseSpanishDutchKlingonSwedishEnglishKoreanThaiEstonianLatvianTurkishFinnishLithuanianUkrainianFrenchMalayUrduGermanMalteseVietnameseGreekNorwegianWelshHaitian CreolePersian //  TRANSLATE with COPY THE URL BELOW Back EMBED THE SNIPPET BELOW IN YOUR SITE Enable collaborative features and customize widget: Bing Webmaster PortalBack//